STUDI PEMBUATAN NUGGET FUNGSIONAL DARI IKAN CAKALANG (KATSUWONUS PELAMIS L.) DENGAN EKSTRAK BUAH MENGKUDU (MORINDA CITRIFOLIA L.): (Studi of Making Fungsional Nugget from Skipjack Fish (Katsuwonus pelamis L.) with Noni Fruit Ekstrak (Morinda citrifolia L.) - Jalil Genesa; Nandi K Sukendar; Shinta Regia (jurnal1, 2018)
Nugget skipjack fish with noni fruit extract is a processed food from fish meat. It is milled with the addition of noni fruit extract as a value added (fuctional) on nugget products. Noni fruit is less favored by people due to the bitter taste and the aroma is sting. Therefore , it was carried out addition of extract from noni fruit on nugget processed products. This research aimed to produce functional nugget product from skipjack fish with noni fruit extract and to know chemical and physical content of nugget and alkaloids content in nugget. The parameters were water content, ash content, fat content, protein content, carbohidrate content, organoleptic test, and alkaloids content. The expremental design was Randomized Block Design with 3 treatments and 3 replications. Alkaloids content was present in all treatments . The best treatment based on physical, chemical, and oreganoleptics test of nugget was F3 treatment (60% fih meat + 7% extract of noni + 23% filler + 10% ice water). Result of organoleptics test texture 3.59 (likes), color 3.48 (rather like), aroma 3.63 (like), and taste 3.77 (like).